Challenges and Strategies of History Teachers in Utilizing Digital Learning Media: A Case Study at SMKN 1 Banjarmasin - Muhammad Aminullah; Heri Susanto; Dewicca Fatma Nadilla; Fitri Mardiani (JURNAL PENDIDIKAN IPS, 2025)
History learning in the digital era requires teachers to adapt their teaching strategies to the characteristics of students who are accustomed to technological environments. This study aims to examine the challenges and strategies of history teachers in utilizing digital learning media at SMKN 1 Banjarmasin. The research employs a qualitative approach with a case study design. Data were collected through classroom observations, semi-structured interviews, and documentation. Informants consisted of two history teachers and ten students from grades X and XI who were directly involved in digital-based learning practices. The findings identified four main challenges: limited technological infrastructure, low digital competence among teachers, psychological barriers such as anxiety over technical disruptions, and time constraints due to administrative burdens. The strategies implemented by teachers included self-directed learning through online resources, peer collaboration, involving students in technical support, and using easily accessible digital media. In addition, some teachers integrated digital media with interactive methods such as quizzes and historical role-playing. These findings indicate that teachers are still able to innovate despite existing limitations. Future researchers are advised to further examine the effectiveness of these strategies on learning outcomes.